2016
DOI: 10.1002/tal.1337
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of precast concrete based dry mechanical column-column joints for precast concrete frames

Abstract: Summary This paper proposed a precast concrete‐based dry mechanical joint for fully‐restrained moment connections which can be used to connect reinforced concrete precast columns. In the proposed connections, a pair of steel plates is provided and connected by high‐strength bolts to transfer axial loads and moments. One plate is installed at the bottom of upper columns, and another one is placed on the top of lower columns. The stiffness of the column plates is determined to enable axial loads and the moment t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The authors obtained test data of Figure 10 in the previous study [24] and found numerical data that matched the test data via finite element analysis based on the tie model established between the two separate surfaces. A numerical investigation of the proposed frames using finite element analysis (FEA) based on concrete plasticity was carried to explore the nonlinear structural behavior of the section.…”
Section: Methodsmentioning
confidence: 99%
“…The authors obtained test data of Figure 10 in the previous study [24] and found numerical data that matched the test data via finite element analysis based on the tie model established between the two separate surfaces. A numerical investigation of the proposed frames using finite element analysis (FEA) based on concrete plasticity was carried to explore the nonlinear structural behavior of the section.…”
Section: Methodsmentioning
confidence: 99%
“…Dry mechanical connections for precast concrete frames were proposed in the previous study of (Hu, Hong, and Park 2017), where mechanical joints for both irregular steel-concrete composite precast frames and reinforced concrete precast frames were developed to replace conventional cast-inplace concretes. An experimental investigation of "L"-shaped precast concrete column joints with laminated mechanical plates was also performed to verify that L-shaped precast columns spliced by laminated metal plates provided fully and partially restrained moment connections (Nzabonimpa and Hong 2019) where brief numerical investigations were presented with limited discussions of microscopic strains to explore damage evolution of structural components of mechanical joints.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Thereby proving the sleeve connections as efficient and strong for mainstream connections [29]. A novel mechanism for column to column connections with detachable slabs have been presented by Hu et al [30] and Nzabonimpa and Hong [31] which are able to pair steel plates connected by high-strength bolts for the transfer of axial load and moment. A hybrid frame method that incorporates the steel core at the joint regions was proposed by Park et al [32] which allow vertical reinforcements at the vertical splicing regions.…”
Section: Literature Reviewmentioning
confidence: 99%